Desafios da política ambiental e de mobilidade urbana de São Carlos (SP): análise das possibilidades e limitações de duas propostas para conclusão do trecho nordeste do anel perimetral proposto nos anos 1970 - Prando, Tales Augusto (Universidade Federal de São Carlos, 2021)
ABSTRACT The aim of this dissertation is the project of a ring road idealized for the city of São Carlos (SP) in the 1970s. Especially on the northeast stretch, interrupted due to environmental infractions. We investigate and discuss the possibilities and limitations of the conclusion. This study is motivated by the relevance of this road connection, which should interconnect important urban sectors of the city that today remain more isolated. To carry out this research, information was collected and compiled in two main aspects, the urban and environmental characteristics of the affected region and the relevant legislation, especially concerning the urban permanent preservation area (under Brazilian law 12.651) and urban planning instruments that could be applied, which involves urban and environmental requalification with provision for re-establishing the road connection. Based on the data analyses, is possible to formulate alternatives path to complete the northeast perimeter, through alternatives path for connection, which allows the identification of their respective possibilities and limitations. This investigation can contribute to future urban public policies concern in restore this important road connection.
Challenges of environmental policy and urban mobility in São Carlos (SP): analisys of the possibilities and limitations of two proposals for completing the northeastern section of the perimeter ring proposed in the 1970s
Keywords: Infraestrutura urbana; Conexões viárias; Mobilidade urbana; APPs urbanas; Instrumentos urbanísticos; São Carlos (SP); Urban infrastructure; Urban road connections; Urban mobility; Urban environmental protection areas; Urbanistic instruments; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA::RECUPERACAO DE AREAS DEGRADADAS; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::SERVICOS URBANOS E REGIONAIS::ASPECTOS FISICO-AMBIENTAIS DO PLANEJAMENTO URBANO E REGIONAL